Effect of cord puncture site in cordocentesis at mid-pregnancy on pregnancy outcomes - Tangshewinsirikul C. (2014)
Objectives: To compare the procedure and pregnancy outcomes of pregnancies undergoing cordocentesis between a group of cord insertion puncture and that of free loop puncture. Materials and Methods: Pregnancies undergoing cordocenteses meeting the following inclusion criteria were recruited: (1) singleton pregnancies at gestational ages of 18-22 weeks; (2) no fetal abnormalities; (3) the procedures performed by experienced operators; and (4) the procedures of no placenta penetration. The recruited cases were classified into two groups: a group of cordocenteses with puncture site at placental cord insertion (Group 1) and those with puncture site at cord free loop (Group 2). The primary outcomes to be compared were rates of fetal loss, newborns with low birth weight and preterm birth. The secondary outcomes included a rate of successful procedures, umbilical cord bleeding, fetal bradycardia, maternal blood contamination, and duration of the procedure time. Results: Of 6147 cordocenteses recruited, 2214 met inclusion criteria. The mean duration to complete the procedure in Group 1 was significantly shorter than that in Group 2 (4.5 ± 5.4 vs 6.7 ± 8.5 min, Student's t-test; p = 0.001). The mean birth weight and gestational age at delivery were comparable between the two groups. No significant differences between the two groups were seen in rates of fetal loss, low birth weight, preterm birth, successful procedures, umbilical cord bleeding, or fetal bradycardia. However, the rate of maternal blood contamination was significantly higher in the group of puncture at the cord insertion site. Conclusion: Of cordocenteses performed based on accessibility and quality of visualization, cord insertion puncture may cause more maternal blood contamination but free loop puncture may be associated with more difficult procedures, while the safety was comparable. © 2011 John Wiley & Sons, Ltd.